Effects of leaf age during drought and recovery on photosynthesis, mesophyll conductance and leaf anatomy in wheat leaves - Jahan, Eisrat; Sharwood, Robert Edward; Tissue, David T. (Frontiers in Plant Science, 2023)
Diffusion of CO2 from the intercellular airspaces to the site of Rubisco within C3 plant chloroplasts (g¬m) governs photosynthetic CO2 assimilation (A). However, variation in gm in response to environmental stress during leaf development remains poorly understood. Age-dependent changes in leaf ultrastructure and potential impacts on gm, A, and stomatal conductance (gs) were investigated for wheat (Triticum aestivum L.) in well-watered and water-stressed plants, and after recovery by re-watering of droughted plants. Significant reductions in A and gm were found for both well-watered and water-stressed plants as individual leaves aged. Plants in water-stressed condition (leaf water potential from -1.0 to -1.8 MPa) showed lowered gs in leaves of all ages, but lowered A and gm in only the youngest leaves (1 day old). When droughted plants were rewatered, the degree of recovery depended on the age of the leaves, with mature leaves (8 days old) showing a stronger recovery than either young or old leaves (15 days old). The rate of decline in A and gm as leaves aged was slower for water-stressed than well-watered plants. The surface area of chloroplasts exposed to intercellular airspaces (Sc) and the size of individual chloroplasts declined as leaves aged, resulting in a positive correlation between gm and Sc. Leaf age significantly affected cell wall thickness (tcw), having higher tcw for old leaves compared to mature/young leaves. These results will help to understand the leaf anatomical traits associated with gm to explain changes due to varying leaf age and plant water status, which will open up more possibilities for improving photosynthesis using breeding/biotechnological strategies.